The EASY (Early Access to Support for You) sickness absence service: a four-year evaluation of the impact on absenteeism - Judith Brown; Daniel Mackay; Evangelia Demou; Joyce Craig; John Frank; Ewan B Macdonald (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: In May 2008, the National Health Service (NHS) Lanarkshire (NHSL) implemented a unique telephone-based sickness absence management service entitled "EASY" (Early Access to Support for You). The EASY service supplements existing absence policies and enables telephone communication between the absentee, their line manager, and the EASY service from the first day of absence and referral to occupational health services at day ten. The aim of this study was to determine if the EASY service was effective between May 2008 and May 2012 in reducing sickness absence in NHSL compared to normal occupational healthcare in NHS Scotland and is, as such, a cost-saving intervention. METHODS: This study included time-series analysis of health board sickness absence data and analyses of the EASY service database (survival analyses and Cox's proportional hazards model). RESULTS: The EASY service was effective in reducing sickness absence by 21% in NHSL, whereas the nonspecific tightening of the sickness absence policies across the rest of Scottish NHS health boards reduced sickness absence by approximately 9%. The richness of the EASY database gave detailed information on absentees by cause, duration, job family, and reporting compliance. The mean duration of musculoskeletal absences was significantly shorter in years 2, 3, and 4 compared to year 1. Those absentees contacted by phone on the first day of absence were more likely to return to work than those contacted on subsequent days. The EASY service improves economic efficiency; the value of the hours saved from the reduced sickness absence exceeds the cost of operating the service. CONCLUSION: The study highlights the importance of an early telephone-based intervention for sickness absence management.